Kajian Risk Profile dan Self Assesment pada Bank Umum Syariah yang Listing di BEI - Ade Rizky Anugerah; Ima Amailah (Bandung Conference Series: Economics Studies, 2023)
Abstract. Measurement of the level of soundness using the CAMELS approach is not yet comprehensive in evaluating the level of bank performance. Therefore, it is used to measure banking performance using RGEC, namely bank health assessment by self-assessment of the bank studied. The purpose of this study is to identify and evaluate the Risk Profile, Good Corporate, Earnings, Capital of Islamic Commercial Banks on the IDX. The method used is quantitative descriptive with secondary data collected from the annual financial reports of Islamic Commercial Banks listed on the Indonesia Stock Exchange from 2019-2022. The banks that are the object of research are BSI, BAS, BTPNS, BPDS. From the results of secondary data classifiers, the results obtained are Risk Profile, GCG, Earnings and capital adequacy of Islamic Commercial Banks listed on the IDX in the good category in 2019, 2021 and 2022. The decline in the performance of Islamic Commercial Banks listed on the IDX occurred in 2020 as an effect the presence of Covid-19. Risk Profile performance reaches two digits, Earning (ROA, ROE, NOM, BOPO) is in poor category, capital availability is less than 6% (poor category) the same thing self assessment for GCG BUS listed on BEI is in bad category at points 3 and 4. Abstrak. Pengukuran tingkat kesehatan dengan menggunakan pendekatan CAMELS belum komperehensif dalam mengevaluasi tingkat kinerja bank. Oleh karena itu, digunakan pengukuran kinerja perbankan menggunakan RGEC yaitu penilaian kesehatan bank dengan self-assessment dari bank yang diteliti. Tujuan dari penelitian ini adalah untuk mengidentifikasi dan mengevaluasi Risk Profile, Good Corporate, Earnings, Capital dari Bank Umum Syariah di BEI. Metode yang digunakan adalah deskriptif kuantitatif dengan data sekunder yang dikumpulkan dari laporan keuangan tahunan Bank Umum Syariah yang listing di Bursa Efek Indonesia dari tahun 2019-2022. Adapun bank yang menjadi objek penelitian adalah BSI, BAS, BTPNS, dan BPDS. Penurunan kinerja Bank Umum Syariah yang listing di BEI terjadi pada tahun 2020 sebagai efek adanya Covid-19. Kinerja Risk Profile mencapai dua digit. Earning (ROA, ROE, NOM dan BOPO) berkategori buruk, ketersediaan modal kurang dari 6% (kategori buruk). Hal yang sama self-assessment untuk GCG BUS yang listing di BEI berkategori buruk, berada di poin 3 dan 4.